2023
DOI: 10.1039/d2nr05140k
|View full text |Cite
|
Sign up to set email alerts
|

High surface area siloxene for photothermal and electrochemical catalysis

Abstract: Catalysis based on two-dimensional silicon has been under intense scrutiny recently. However, its substandard catalytic activity is far from industrialization. In this work, we demonstrate a new solution to this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Under identical photothermal CO 2 hydrogenation conditions, our K + −Co−C catalyst shows a stable CO formation rate of 758 mmol g cat −1 h −1 with a 99.8 % selectivity (Figure 3b blue). This CO rate is at least 4 times higher than other CO 2 hydrogenation catalysts tested under similar conditions (Figure 3c and Table S3) [13–16,18,20,28–32] . When normalized to the mass of Co, the CO production rate is 2871 mmol g Co −1 h −1 with an estimated TOF of 4.65 s −1 , superior to all other Co‐based photothermal CO 2 hydrogenation catalysts reported to date (Table S2) [19,21,33–38] .…”
Section: Figurementioning
confidence: 64%
See 1 more Smart Citation
“…Under identical photothermal CO 2 hydrogenation conditions, our K + −Co−C catalyst shows a stable CO formation rate of 758 mmol g cat −1 h −1 with a 99.8 % selectivity (Figure 3b blue). This CO rate is at least 4 times higher than other CO 2 hydrogenation catalysts tested under similar conditions (Figure 3c and Table S3) [13–16,18,20,28–32] . When normalized to the mass of Co, the CO production rate is 2871 mmol g Co −1 h −1 with an estimated TOF of 4.65 s −1 , superior to all other Co‐based photothermal CO 2 hydrogenation catalysts reported to date (Table S2) [19,21,33–38] .…”
Section: Figurementioning
confidence: 64%
“…This CO rate is at least 4 times higher than other CO 2 hydrogenation catalysts tested under similar conditions (Figure 3c and Table S3). [13][14][15][16]18,20,[28][29][30][31][32] When normalized to the mass of Co, the CO production rate is 2871 mmol g Co À 1 h À 1 with an estimated TOF of 4.65 s À 1 , superior to all other Co-based photothermal CO 2 hydrogenation catalysts reported to date (Table S2). [19,21,[33][34][35][36][37][38] K + À CoÀ C synthesized from KNO 3 and KCl show similar CO productivity and selectivity, demonstrating that the performance improvement is indeed caused by K + .…”
Section: Zuschriftenmentioning
confidence: 90%
“…52−54 For example, Su et al demonstrated that the siloxene prepared by reacting CaSi 2 with concentrated HCl at low temperature exhibited a surface area of 17 m 2 /g; however, the surface area increased to 159 m 2 /g upon removal of bulk Si using NaOH prior to deintercalation of CaSi 2 . 54 The conductivity of the siloxene-0, -1, -4, and -4P electrodes was measured using the four-point probe method and was very similar, ranging from 2 to 6 × 10 −4 S cm −1 for all electrode types.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The observation of significantly higher surface area of the purified siloxene-4P material relative to unpurified siloxene-0, 1, and 4 samples is attributed to the absence of bulk silicon in the purified siloxene-4P sample. Previously reported values of the surface area of siloxene vary widely and may be dependent of the synthetic conditions. For example, Su et al demonstrated that the siloxene prepared by reacting CaSi 2 with concentrated HCl at low temperature exhibited a surface area of 17 m 2 /g; however, the surface area increased to 159 m 2 /g upon removal of bulk Si using NaOH prior to deintercalation of CaSi 2 . The conductivity of the siloxene-0, -1, -4, and -4P electrodes was measured using the four-point probe method and was very similar, ranging from 2 to 6 × 10 –4 S cm –1 for all electrode types.…”
Section: Resultsmentioning
confidence: 99%
“…The large surface area was advantageous to trap light and expose more active sites in full contact with contaminants and PMS. 11,37 Further, the chemical compositions of the as-obtained CNG-800 were identified by XPS. The investigated results revealed the presence of C (81.44%), N (9.42%), O (8.63%), and Co (0.61%) in CNG-800 (Figure 3c).…”
Section: Characterization Of Cng-800mentioning
confidence: 99%